2012
DOI: 10.1016/j.ygcen.2012.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Identification of ovarian gene expression patterns during vitellogenesis in Atlantic cod (Gadus morhua)

Abstract: Follicular maturational competence and ovulatory competence in teleost fish refer to the ability of the ovarian follicle to undergo final oocyte maturation and ovulation, respectively, in response to gonadotropin stimulation and other external cues. Some gene products related to competence acquisition are likely synthesized during vitellogenic growth, as these follicles gain in vivo responsiveness to exogenous gonadotropin stimulation and can be induced to undergo maturation and ovulation. In Atlantic cod (Gad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 73 publications
2
17
0
Order By: Relevance
“…Similarly, we observed that ucp2 and star expression increases from early‐ to late‐vitellogenic oocytes in cod. The associated cyp11a1 and cyp19a1 , which are essential for estradiol‐17β synthesis (reviewed by Uno et al, ), show similar expression profiles to star , partly in agreement with the findings of Breton et al (). Increased expression of star , cyp19a1 , and cyp11a1 increases the steroid synthesis capacity, including the production of estradiol‐17β, which is increased in parallel with follicle‐stimulating hormone (FSH) in coho salmon plasma during cortical alveoli synthesis.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Similarly, we observed that ucp2 and star expression increases from early‐ to late‐vitellogenic oocytes in cod. The associated cyp11a1 and cyp19a1 , which are essential for estradiol‐17β synthesis (reviewed by Uno et al, ), show similar expression profiles to star , partly in agreement with the findings of Breton et al (). Increased expression of star , cyp19a1 , and cyp11a1 increases the steroid synthesis capacity, including the production of estradiol‐17β, which is increased in parallel with follicle‐stimulating hormone (FSH) in coho salmon plasma during cortical alveoli synthesis.…”
Section: Discussionsupporting
confidence: 83%
“…Apart from the biological results, our results may differ from previous studies of the cod transcriptome in follicles and early embryos due to different methods applied, sample types, and number of genes assayed per sample. For example, we measured gene expression in isolated follicle cells with a certain size range, whereas other studies used heterogenous ovary tissue (Goetz et al, ; Breton et al, ; Breton and Berlinsky ), which in addition to follicle cells of different size ranges contains connective cells. Hence, using whole‐ovary samples from cod may introduce heterogeneity in data since a mix of stage‐specific processes during oogenesis are being monitored.…”
Section: Discussionmentioning
confidence: 99%
“…Along with AFP4s have been identified in temperate, subtropical and tropical fishes that have no need to prevent freezing 20, 24, 25, their biological roles have been speculated to bind to lipid or ligand other than ice because of the helix bundle structure similarity to certain apolipoproteins (Apos) 24, 26, 28, but the exact physiological functions have been unknown up to the present. Our current study has revealed the biological roles of AFP4a and AFP4b in embryonic development, and has confirmed that AFP4a and AFP4b contribute to epiboly progression and convergence movement during early zebrafish embryogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The complete sequences of other functionally characterized AFP4s in Myoxocephalus octodecemspinosus ( Mo ) 23, 26, Pleuragramma antarcticum ( Pa ), Notothenia coriiceps ( Nc ) 25 and Gadus morhua ( Gm ) 27, 28 were downloaded from GenBank non-redundant protein database. An unrooted maximum likelihood (ML) phylogenetic tree of AFP4s was constructed by MEGA 6 34 with 1000 bootstrap replications, in which their evolutionary distances were computed using the JTT+F model, which was selected by ProtTest 2.4 35 based on the corrected Akaike information criterion.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation